Pengaruh Pendekatan Realistic Mathematics Education (RME) Terhadap Hasil Belajar Matematika Pada Siswa Kelas V SDN Lembaya Kabupaten Gowa - Nurmi Hasrawati; Baharullah Baharullah; Khaerul Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find out how big the mathematics learning outcomes are through the Realistic Mathematics Education (RME) learning approach and whether there is an influence of the Realistic Mathematics Education (RME) learning approach on the mathematics learning outcomes of fifth grade students at SDN Lembaya, Gowa Regency. This type of research is a type of quantitative research. The design in this research is Quasi Experimental Design. The population and sample were 50 class V students at SDN Lembaya, Gowa Regency. The instruments in this research are tests and observation sheets. The data that has been collected using existing instruments is then analyzed quantitatively using descriptive and inferential analysis techniques.The results of the research show that the student learning outcomes in the experimental class using the Realistic Mathematics Education (RME) approach obtained an average score of 80 and a complete KKM score, namely a frequency of 25 students with a percentage of 100% of class V students at SDN Lembaya, Gowa Regency. There is an influence of the Realistic Mathematics Education (RME) approach on mathematics learning outcomes for class V students at SDN Lembaya, Gowa Regency. The t test results show tcount of 3.873. The ttable value of α = 0.05 and dk = 50 – 2 = 48 is 2.009, so the result obtained is tcount > ttable, namely 3.873 > 2.009. Based on these results, H0 is rejected and H1 is accepted.